Tropical and temperate shrimps response to global warming: a comprehensive physiological and biochemical comparison - Neves, Manuel de Carreira Lopes e Marques, 1988- (2013)
Tese de mestrado. Biologia (Ecologia Marinha). Universidade de Lisboa, Faculdade de Ciências, 2013